Transformation of Palembang malay community cultural values based on character education in dance learning in higher education - Halimah Agustina; Malarsih Malarsih; Deasylina da Ary (Pascasarjana Institut Seni Indonesia Surakarta, 2022)
This research was analyzed with the aim of uncovering and knowing the transformation of the local culture of the Palembang Malay community, which has values in activities, art, or symbolic meanings that characterize the character of the local community which can be used as character enrichment in dance learning in tertiary institutions with a culture based on material content local Problem formulation; (1) what character values do Palembang Malay people have in the form of the Tanggai Dance art; (2) how is the transformation of culture-based character values in dance learning which is used as content material in Higher Education. This study uses a qualitative research method described and analyzed through an interdisciplinary approach to using a case study design in learning the Tanggai Dance at PGRI Palembang University, Department of Performing Arts Education. Data collection was carried out through observation, interviews and document study through an interactive analysis model. The results of the study show that the cultural values of the Malay people of Palembang originate from the habit of activities that give rise to art forms in the Tanggai Dance by holding the philosophy of rasan tuo and the motto of the meaning of sendok piyogo so that it is used as a reference for reflecting on character-based material content in learning Regional Dance at PGRI Palembang University which produces value in learning activities. The transformation process involves students, lecturers, and creators of the Tanggai Dance. Empirically the implementation of learning activities in schools and communities occurs in material content as a source of learning, while the Tanggai Dance functions as a work of art that has philosophy, history, and meaning in the form of dance so that Tanggai Dance is used as local culture-based material content to develop student character in Universities as prospective educators